2007
DOI: 10.1086/519925
|View full text |Cite
|
Sign up to set email alerts
|

An Imaging Survey for Extrasolar Planets around 45 Close, Young Stars with the Simultaneous Differential Imager at the Very Large Telescope and MMT

Abstract: We present the results of a survey of 45 young (P250 Myr), close (P50 pc) stars with the Simultaneous Differential Imager (SDI) implemented at the VLT and the MMT for the direct detection of extrasolar planets. As part of the survey, we observed 54 objects, consisting of 45 close, young stars; two more distant (<150 pc), extremely young (10 Myr) stars; three stars with known radial velocity planets; and four older, very nearby (20 pc) solar analogs. Our SDI devices use a double Wollaston prism and a quad filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
177
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(185 citation statements)
references
References 70 publications
(93 reference statements)
8
177
0
Order By: Relevance
“…These constraints on the planet population are consistent with previous survey analyses (Biller et al 2007;Nielsen & Close 2010;Chauvin et al 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These constraints on the planet population are consistent with previous survey analyses (Biller et al 2007;Nielsen & Close 2010;Chauvin et al 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Direct imaging is a detection method that allows us to characterize large-separation exoplanets. In the past decade many direct imaging surveys (e.g., Lowrance et al 2005;Biller et al 2007;Lafrenière et al 2007;Chauvin et al 2010;Heinze et al 2010;Vigan et al 2012;Biller et al 2013;Rameau et al 2013a;Wahhaj et al 2013;Chauvin et al 2015;Brandt et al 2014a;Bowler et al 2015) have been carried out to evaluate the occurrence of giant planets in wide orbits (10-500 AU).…”
Section: Introductionmentioning
confidence: 99%
“…(b) They inferred the planet population from boundaries in a planet mass-semi major axis grid considering a disk instability model. (c) They performed their analysis using results from surveys of Masciadri et al (2005), Biller et al (2007), and Lafrenière et al (2007). (d) They inferred the planet population from power law distributions with different coefficients of m and a that were used in Cumming et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, numerous large DI surveys to detect giant planet companions have reported null-detections (Masciadri et al 2005;Biller et al 2007;Lafrenière et al 2007;Ehrenreich et al 2010;Chauvin et al 2010;Janson et al 2011;Delorme et al 2012), but this allowed set upper limits to the occurrence of giant planets. Table 1 reports the statistical results of several DI surveys as a function of the sample, separation and mass ranges, and planet distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The signal of the companion will thus be partially preserved after the subtraction. SDI was first used on the Canada France Hawaii Telescope (CFHT) with the TRIDENT camera (Marois et al 2000(Marois et al , 2003a, with NaCo on the Very Large Telescope (VLT/NaCo; Lenzen et al 2003;Rousset et al 2003) and with the Multiple Mirror Telescope (MMT) A&A 581, A80 (2015) by Close et al (2005) and Biller et al (2007). Recently, Close et al (2014) confirmed a close-in companion around HD 142527 with SDI with MagAO, based on a detection of the Hα emission, not a molecular absorption.…”
Section: Introductionmentioning
confidence: 99%